TRAGICITY AND FEMININE IDENTITY IN CONTEMPORARY UZBEK POETRY: A POETIC STUDY OF SUBJECTIVITY AND MEMORY - Abdusalomova Durdonakhon Valilullo qizi (Scholar Express Journal, 2025)
This article investigates the intersection of tragicity and feminine identity in the works of three leading Uzbek women poets: Zebo Mirzo, Halima Ahmad, and Nodira Ofoq. Through close textual analysis and theoretical frameworks including Pospelov’s theory of tragic conflict, Butler’s gender performativity, Kristeva’s abjection, and Camus’s absurdism, the study demonstrates how these poets transform personal grief and cultural silence into lyrical resistance. The poetic “I” in their verse is not a passive voice of suffering, but an active, fragmentary subject engaging in aesthetic survival. The study contributes to feminist literary criticism and post-Soviet Uzbek poetics.
Keywords: tragic conflict; feminine identity; lyrical subject